The Islamic Law's Implementation About Waqf - Mustafa Mustafa (Proceeding International Seminar of Islamic Studies, 2019)
The problem is that the basis for the agreed upon legal source of wakefulness is very limited. The waqf researcher did not find an excerpts from the Koran about his study of waqf. Normally, the basis for the rain is hadis' umar ibn khattab when acquiring part of the land of khaibar and meaning to represent it. This gift can further interpret the practice and management of waqff. It's just that this ambiguous reference to the messenger of god's messenger is also very limited. Ijtihad therefore is the most sound solution for problems in waqf which is increasing. According to clerics of the waaf law sunnah, whereas hanfiyah sheikh hanfiyah said that waqf's law was muaba (may) because in his opinion even non-muslims could forgive part of his wealth and its law is legal. All scholars also agree that the one who agreed to the benefit of some of his assets was a shaleh charity found in the Islamic sharia.